Practical Barriers to Medication Adherence: What Do Current Self- or Observer-Reported Instruments Assess? - Chan, Amy Hai Yan; Cooper, Vanessa; Lycett, Helen; Horne, Rob (Frontiers in Pharmacology, 2020)
Introduction: Practical adherence barriers (e.g. medication frequency) are generally more amenable to intervention than perceptual barriers (e.g. beliefs). Measures which assess adherence barriers exist, however these tend to measure a mix of factors. There is a need to identify what practical barriers are captured by current measures. Aim: To identify and synthesise the practical adherence barriers which are assessed by currently available self- or observer-report adherence measures. Methods: A search for systematic reviews of self- or observer-report report adherence measures was conducted. Three electronic databases (Embase, Ovid Medline, and PsycInfo) were searched using terms based on adherence, adherence barriers and measures. Systematic reviews reporting on adherence measures which included at least one self- or observer-report questionnaire or scale were included. Adherence measures were extracted and coded on whether they addressed perceptual or practical barriers, or both. Practical items were then analysed thematically. Results: Following screening of 272 initial abstracts, 20 full-text papers were reviewed. Four were excluded after full-text review, leaving 16 systematic reviews for data extraction. From these, 187 different adherence measures were extracted and coded, and 23 unique measures were identified as assessing practical barriers and included in the final analysis. Seven key themes were identified: formulation; instructions for use; issues with remembering; capability – knowledge and skills; financial; medication supply and social environment. Conclusion: Existing adherence measures capture a variety of practical barriers which can be grouped into seven categories. These findings may be used to inform the development of a measure of practical adherence barriers.